Macro and microstructural analysis in a shear zone of the Sevilla metamorphic province: Sierra Nevada de Santa Marta, Colombia (2019)
Macro and microstructural evidence collected in the field and the laboratory confirm the existence of four deformation events in a shear zone in the north-western part of the Sevilla metamorphic belt in the Sierra Nevada de Santa Marta. The D1, D2, and D3 deformations are associated with folding processes of the tectonic S0, S1, and S2 surfaces. These deformations occurred in a ductile environment. A shear zone oriented N-S defines the last event $D_4$. The shear zone develops in a transpressive margin as a result of the oblique convergence between the Caribbean plate to the northern margin of the South American plate. The petrographic and micro tectonic analysis allowed to determine prograde and retrograde metamorphic facies and the intracrystalline deformations that support the deformation phases in the rock units described above. The identified deformations allowed to create a tectonic model in a temporal and spatial context that links the collected evidence with regional tectonic events.